2023
DOI: 10.1039/d3sc03081d
|View full text |Cite
|
Sign up to set email alerts
|

Trialkylphosphonium oxoborates as C(sp3)–H oxyanion holes and their application in catalytic chemoselective acetalization

Vincent Ming-Yau Leung,
Hong-Chai Fabio Wong,
Chun-Man Pook
et al.

Abstract: The use of trialkylphosphonium oxoborates (TOB) as catalysts is reported. The site-isolated borate counter anion in a TOB catalyst increases the availability of the C(sp3)-H to interact with electron donor...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…It was found that the acetate anion did not position at the center above the cyclopropenium cation. Instead, the oxygen anion was found to position close to the C(sp 3 )–Hs of cyclohexyl groups with C–H···O distance ∼2.8 Å, suggesting that the cyclopropenium system might interact with the electron donor via NCHB interactions. , NMR titration experiment was conducted. Hexamethylphosphoramide (HMPA) which is a stronger hydrogen bond acceptor was used to obtain more obvious signals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the acetate anion did not position at the center above the cyclopropenium cation. Instead, the oxygen anion was found to position close to the C(sp 3 )–Hs of cyclohexyl groups with C–H···O distance ∼2.8 Å, suggesting that the cyclopropenium system might interact with the electron donor via NCHB interactions. , NMR titration experiment was conducted. Hexamethylphosphoramide (HMPA) which is a stronger hydrogen bond acceptor was used to obtain more obvious signals.…”
Section: Resultsmentioning
confidence: 99%
“…Hexamethylphosphoramide (HMPA) which is a stronger hydrogen bond acceptor was used to obtain more obvious signals. The cyclohexyl C­(sp 3 )–Hs of A shifted upfield and broadened gradually when the amount of HMPA was increased, attributed to the electron donation to the C­(sp 3 )–Hs via NCHB (Figure D) . On the other hand, the 77 Se signal has only negligible change (see SI, Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…[20] Recently, we have developed trialkylphosphonium oxoborate (TOB) catalysts for chemoselective acetalization. [21] Different from many phosphonium salts that could act as Lewis acids, [22] it was found that the TOB catalysts have a group of preorganized C(sp 3 )À Hs that could serve as oxyanion holes to stabilize the developing anionic intermediates via NCHB during the transition state. TOB catalysts were found to be stronger NCHB donors than some typical onium salts because the counter-anion (borate) is siteisolated so that the C(sp 3 )À Hs in TOB are not occupied and more available to interact with substrates.…”
Section: Introductionmentioning
confidence: 99%